Organizational performance and change management workshop proceedings - International Institute of Rural Reconstruction (Silang, Cavite International Institute of Rural Reconstruction, 1998)
There are endless variables in the process of change. No variable is more challenging, or more enriching, than the variable of human choice. Development organizations that support human choice participatory approaches whilst working with communities, know that these approaches bear their own seeds of success, along with the seeds of change and, often, constraint.

Organizations that aspire to be change agents must themselves, ourselves, become learning agents. One need only spend time at the family dinner table to appreciate the value, over time, of letting disparate voices contribute to the growth of each and all. Silent voices can be deafening.

Development organizations do not perform in isolation of one another within the same arena. Success of one of us need not come at the expense of others of us. No. We can best succeed in our missions by drawing on and contributing to the success of each other. The documented workshop proceedings gives cases for all to learn from.
Overview
The external context of NGDO's
The internal impetus and imperatives for organizational performance and change management

Workshop 1
Critical factors and performance indicators
Case 1: Sibol ng Agham at Teknolohiya (SIBAT) experience performance indicators
Case 2: The question for a transformed organization
A review of factors in organizational performance in a Christian development organization (World Vision, Incorporated)
Comments on the cases
Workshop outputs
Summary of discussions

Workshop 2
Performance assessment frameworks, tools and techniques
Case 3: Planning, monitoring and evaluation: the PhilDHRRA experience
Case 4: MASAI: experiences in developing and using organizational assessment tools
Comments on the cases
Workshop outputs
Summary of discussions

Workshop 3
Change management
Case 5: Philippine Business for Social Progress (PBSP): organizational change management
Case 6: Pambansang Kilusan ng mga Samahang Magsasaka (PAKISAMA): a case of PO autonomy
Comments on the cases
Workshop outputs
Summary of discussions

Workshop synthesis
Workshop synthesis
Comments and action plans

Annexes
Annex 1: Directory of participants
Annex 2: Organizational capacity assessment tool
Annex 3: Reflections on Philippine NGO organizational performance and change management
Annex 4: Sample of indicators used by PhilDHRRA in its 1995-1996 social review
Annex 5: Globalization: dominant trends
Annex 6: Key points in the preliminary review of the literature
Annex 7: References
Includes bibliographical references (pages [227]-228).
Keywords: Non-governmental organizations -- Philippines -- Congresses; Rural development -- Philippines -- Congresses